ВОПЛОЩЕНИЕ ТЕОРЕТИЧЕСКИХ УСТАНОВОК ЮЛИАНА ТУВИМА ВЕГО ИСКУССТВЕ ПОЭТИЧЕ¬СКОГО ПЕРЕВОДА - Piątkowska, Józefina (Vertimo studijos, 2017)
The first purpose of this article is to summarize and present Julian Tuwim’s theoretical views on poetry translation. The poet did not leave any regular work on that matter, despite having been perceived as one of the greatest translators (especially from Russian into Polish). In order to collect Tuwim’s ideas, the author of the article studied his letters, humorous essays and the interviews he had given. The second part of the article is aimed at checking whether Tuwim’s theoretical approach is reflected in his own translation. The reader will be provided with the analyses of Tuwim’s version of Alexander Pushkin’s poem “The Prophet”.